O abigeato e o agronegócio em Dom Pedrito - (:unkn) unknown (Universidade Federal do Pampa, 2012)
The farming plays a fundamental role in Dom Pedrito, not only in the economic and tax, but also in social and cultural formation. Insecurity in rural areas is directly related to the region of the Campanha, having a large territory, including dry border with Uruguay, presents itself as one of the most productive state in the livestock sector and agriculture. This work relates police reports, geographic, historical and cultural referent cattle-rustling in Dom Pedrito, showing features and variations on this crime. Are related to periods of increased occurrence of it, the projects and actions that public agencies adopt for its control in the municipality. Quantifies how much the farmer loses the sale and purchase of illegal animals and how the city government is also impaired in relation to ICMS that has ceased to collect the final consumer who loses by buying meat without knowing the origin that can cause diseases and improvements to lose your city because of taxes that the city failed to raise, in short all sectors of society suffer losses.
Keywords: Furto de animais; Economia; Arrecadação; Theft of animals; Collection; Economics; Agronegócio; Agribusiness; CNPQ::CIENCIAS EXATAS E DA TERRA